Perancangan Usaha dan Kelayakan Pembukaan Usaha Kinar Mete di Kota Surabaya - Ramadhanti, Rezika; Chumaidiyah, Endang; Prambudia, Yudha (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Kinar Mete is a business in the food sector, especially selling cashew nuts, which has been established in 2008 with its production center in Wonogiri. The increasing public interest and consumption of nuts has made the owner of Kinar Mete see the opportunity to expand his business to the city of Surabaya. The feasibility analysis method is used to assess the feasibility of business expansion which includes market, technical, financial aspects as well as sensitivity and risk analysis. The market aspect study obtained from the results of distributing questionnaires to the people of Surabaya City shows that the potential market is 85.33%, the available market is 74%, and the target market is 0.07%. The technical aspect study shows that the business building covers an area of 260 m2 with a workforce of 4 people with working hours Monday-Friday 07.30-16.30 WIB. Financially, the project costs required are IDR 472,955,940. The results of the feasibility study show an NPV of IDR 326,737,829, an IRR of 27.89%, and a PBP of 4.13 years, which shows that the business is worth establishing. Sensitivity analysis shows that business feasibility is sensitive to an increase in raw material costs of 22.38%, labor costs of 57.68%, a decrease in demand of 11.74%, and selling prices of 8.90%. Risk analysis shows that the risk presentation that can occur is 6.35% so that the MARR with a risk of 16.35% results in an NPV value of IDR 180,581,654, an IRR of 27.89%, and a PBP of 4.37 years, which indicates the business remains viable.